2022
DOI: 10.14245/ns.2244092.046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Failure After Total En Bloc Spondylectomy and Salvage Surgery

Abstract: Objective: Total en bloc spondylectomy (TES) is a curative surgical method for spinal tumors. After resecting the 3 spinal columns, reconstruction is of paramount importance. We present cases of mechanical failure and suggest strategies for salvage surgery.Methods: The medical records of 19 patients who underwent TES (9 for primary tumors and 10 for metastatic tumors) were retrospectively reviewed. Previously reported surgical techniques were used, and the surgical extent was 1 level in 16 patients and 2 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For instance, Matsumoto et al reported internal fixation failure in six out of 15 TES cases, with an average occurrence time of 28.3 months [ 4 ]. In a follow-up study by Kwon et al [ 21 ] mechanical failure was observed in three out of 19 patients with primary tumours (33%) and two patients with metastatic tumours (20%). In Liu et al [ 16 ] study, internal fixation breakage was observed in six out of 18 patients with giant cell tumours.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Matsumoto et al reported internal fixation failure in six out of 15 TES cases, with an average occurrence time of 28.3 months [ 4 ]. In a follow-up study by Kwon et al [ 21 ] mechanical failure was observed in three out of 19 patients with primary tumours (33%) and two patients with metastatic tumours (20%). In Liu et al [ 16 ] study, internal fixation breakage was observed in six out of 18 patients with giant cell tumours.…”
Section: Discussionmentioning
confidence: 99%